Admission of patients in psychotic crisis in prodromal stage - Fonseca, Leonardo Leão Kahey; Araújo, Leandro Martins Costa de; Godoy, Emanuele de Freitas Manata; Botti, Nadja Cristiane Lappann (Journal of Health Care, 2017)
Introduction: The experience of the psychotic crisis is a psychopathological condition responsible for the breakup of various aspects of the life of the person, interfering with his functions and roles. Objective: Know the contexts present in the lives of psychotic patients on admission for treatment in the prodromal phase of the crisis. Methodology: A qualitative case study from the Thematic Content Analysis CategorÂical of 100 patients admitted with prodromal symptoms for the treatment of psychotic crisis in PsychoÂsocial Care Center of Brazil. Results: Found as contexts in the lives of patients in the prodromal phase of psychosis the bonds of disruptions, of identity, of psychiatric treatment and emotional rupture, as well as violence and drug abuse during the psychotic crisis. Conclusion: Important to know the contexts in the lives of patients in the prodromal phase of psychosis in order to facilitate early intervention and thus better access to treatment and prognosis.
Keywords: Psychotic disorders; Patient admission; Mental health; Qualitative research